Direct experience while eating: Laboratory outcomes among individuals with eating disorders versus healthy controls. (December 2017) - Elices, Matilde; Carmona, Cristina; Narváez, Vanessa; Seto, Victoria; Martin-Blanco, Ana; Pascual, Juan C.; Soriano, José; Soler, Joaquim
Abstract: Objective: To compare individuals with eating disorders (EDs) to healthy controls (HCs) to assess for differences in direct engagement in the eating process. Method: Participants ( n = 58) were asked to eat an orange slice. To assess the degree of direct engagement with the eating process, participants were asked to write down 10 thoughts about the experience of eating the orange slice. Next, the participants were instructed to classify the main focus of each thought as either experiential ("direct experience") or analytical ("thinking about"). A direct experience index (DEI) was computed by dividing the number of times that participants classified an experience as a "direct experience" (the numerator) by the total number of all observations (i.e., direct experience + thinking about). Participants also completed the Five Facet Mindfulness Questionnaire (FFMQ) and the Experiences Questionnaire (EQ) to assess mindfulness facets and decentering, respectively. Results: Compared to controls, participants in the EDs group presented significantly lower levels of direct experience during the eating task (EDs group: mean = 43.54, SD = 29.64; HCs group: mean = 66.17, SD = 22.23, p = 0.03). Participants in the EDs group also scored significantly lower on other mindfulness-related variables. Discussion: These findings suggest that engagement with the direct experience of eating is lower in individuals with EDs. Future research should investigate the role of mindfulness-based interventions to address direct experience while eating in individuals with EDs. Highlights: Individuals with EDs present low levels of direct experience while eating. Individuals with EDs present low levels of mindfulness and decentering. An association between direct experience and describing and non-reacting was found.